Media Framing on the Palestine-Israel Conflict - Harun Arrosyid; Umi Halwati (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2021)
The media is a medium for acquiring information, presenting factual information, data accuracy, and holding the responsibilities of news writers and media ethics. With the media’s significant role in constructing information and news, the media should be unbiased. However, the media has its pattern of publishing news, such as the conflict between Israel and Palestine. These contrasts can be seen from the various framing between one media and another, such as the different points of view of news writing, the title, and the images displayed. The purpose of this study is to examine how the media reconstructs the reality of the Palestinian-Israeli conflict. The mass media studied were kompas.com and republika.co.id. The research method uses qualitative research with framing analysis of William A. Gamson and Andre Modigliani. Utilizing framing analyst William A. Gamson, the reality emerges in device framing devices and reasoning devices. The results showed that republika.co.id highlighted the news of the United Nations Security Council, which failed to handle the Israeli-Palestinian conflict and tried to raise the image of Palestine, which desperately needed international support. Meanwhile, kompas.com reported on the conflict more neutrally, reporting the United Nations Security Council’s exertions to stop the conflict.